2015
DOI: 10.1007/s10453-015-9387-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pollen load on quality of life: a questionnaire-based study in Lithuania

Abstract: Populations worldwide have been increasingly affected by allergic rhinitis associated with pollen allergens. Alterations in the geographical distribution of pollinating flora resulting from climatic changes and increased production of pollens caused by higher atmospheric CO 2 , have changed the environment in which humans reside. This study, carried out in Lithuania, aimed to demonstrate how people with pollen allergy are affected by symptoms associated with changing pollen loads and to evaluate the resultant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(42 reference statements)
1
15
0
Order By: Relevance
“…A high frequency and a dominant percentage of Poaceae pollen in the microscopic slides of bee bread from the Moravian Valley was also found by Warakomska et al [22], whilst Wróblewska [15] and Wróblewska et al [11] observed the same for bee bread from the area of Podlasie and northeastern Poland. This is also confirmed by the reports of Sá-Otero et al [12] from northwestern Spain, by Atanassova and Lazarova [25] from Bulgaria, and by Šauliené et al [13] from Lithuania. These authors very frequently recorded Poaceae pollen in the microscopic image of pollen loads collected from bees.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A high frequency and a dominant percentage of Poaceae pollen in the microscopic slides of bee bread from the Moravian Valley was also found by Warakomska et al [22], whilst Wróblewska [15] and Wróblewska et al [11] observed the same for bee bread from the area of Podlasie and northeastern Poland. This is also confirmed by the reports of Sá-Otero et al [12] from northwestern Spain, by Atanassova and Lazarova [25] from Bulgaria, and by Šauliené et al [13] from Lithuania. These authors very frequently recorded Poaceae pollen in the microscopic image of pollen loads collected from bees.…”
Section: Discussionsupporting
confidence: 87%
“…In Poland, the interest of bees in collecting oak pollen was confirmed by Wróblewska et al [11], who found Quercus pollen grains in bee bread from the northeastern region of Poland. Sá-Otero et al [12] also demonstrate that Quercus pollen occurred in pollen loads of honeybees in northwestern Spain, whereas Šauliené et al [13] found its presence in pollen loads in Lithuania. Maurizio and Grafl [14] stress that honeybees do not readily visit male inflorescences of Pinus.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2013, the pollen season in Lithuania started later than usual [19] and extended from April until September (Fig. 4).…”
Section: Airborne Pollen Resultsmentioning
confidence: 99%
“…It is the fourth most abundant tree in Lithuanian forests with an occurrence of around 8.5% [39]. Black alder is one of the earliest flowering plants producing abundant content of allergenic pollen [40].…”
Section: Pollen Samplesmentioning
confidence: 99%